Representasi perempuan dalam film Gulliver’s Travels: A Voyage to Lilliput (2010) - Nabila, Syarifah (Maliki Interdisciplinary Journal, 2024)
The role of a woman in the eyes of the man who loves her can reveal a person’s true character. This study aims to determine the role of women in building the plot of the movie Gulliver’s Travels: A Voyage to Lilliput. The selection of this movie is based on the message contained in it. Wrapped with the story of the journey of a number of men to achieve their dreams as well as their romance. This movie is a translation of the prose by Jonathan Swift, which was very popular in ancient times. Data collection uses qualitative methods with documentation techniques. The data was analyzed by reducing and classifying the findings. The results of the study state that all efforts made by men lead to women who are used as their goals. In addition, a person’s attitude in achieving his mission must be in accordance with the benefit of mankind, namely in a good way. This research provides an illustration of the condition of the people who always live their dreams in their own way.